Dynamics of tephra fallout and column collapse during Plinian eruptions of Mt. Pelée volcano (Lesser Antilles): The 2.5 ka cal BCE P5 eruption - Guillaume Carazzo; Audrey Michaud-Dubuy; Vincent Bellier; Benoit Vittecoq (Journal of Volcanology and Geothermal Research, 2025)

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Montagne Pelée volcano (Martinique, in the French Lesser Antilles) hydrogeological system revealed by high-resolution helicopter-borne electromagnetic imagery - Benoit Vittecoq; Pierre-Alexandre Reninger; Vincent Bellier; Anne-Lise Taïlamé; Laureen Nacimento; Emile Gros; Sophie Violette (Hydrogeology Journal, 2023)
Montagne Pelée, on the French island of Martinique, eastern Caribbean Sea, has been one of the deadliest volcanoes in the world, with 30,000 victims following the 1902 eruption. Thousands of people still live nearby, and this volcano is a strategic “water tank” for Martinique Island, providing 40% of the island’s water supply. This research aimed to better understand its hydrogeological functioning and the relationship with its complex volcanological evolution, taking advantage of a high-resolution helicopter-borne geophysical survey correlated with hydrogeological data from the boreholes and springs databases. Electromagnetic data, correlated with hydrogeological data, allowed for the identification of unsaturated zones, aquifers, and seawater intrusions, as well as the main geological units. In addition, data synthesised from pumping tests revealed that the older the unconsolidated pyroclastic deposits, the lower their hydraulic conductivity. The structural asymmetry between the northeastern and southwestern volcano flanks impacts its hydrogeological functioning. Consequently, the Montagne Pelée hydrogeological conceptual model is marked by several distinguishable aquifers. The upper perched aquifer within recent lava domes is directly involved in, and impacted by, phreatic eruptions, and it supports low flowrate springs. The remaining effective rainfall infiltrates to depth and recharges the hydrothermal system through vertical fractures. The other aquifers are categorized into three groups: northeastern, southeastern and southwestern flank aquifers. This research is a new step toward a better understanding of the Lesser Antilles volcanoes and more broadly of the central and proximal parts of the andesitic active volcanoes.